The pharmacological effects of novel isosorbide-based butyrylcholinesterase inhibitors - Khan, Denise (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2009)
This study sought to determine the pharmacological effects of novel isosorbide-based butyrylcholinesterase inhibitors (BuChEl’s) in vitro and in vivo. The potency of the novel compounds 2-benzylcarbamate 5-nicotinate (compound 21), 2-benzylcarbamate 5-salicylate (compound 30), mono-ethyl carbamate 5-salicylate (compound 33), isosorbide-2-benzylcarbmate 5 benzoate (compound 51) and isosorbide-2- butylcarbamate 5-benzoate (compound 57) were assessed in human and mouse plasma using the Ellman assay.The most potent compounds were then profiled in vivo in a mouse model using a protocol based upon the Shirpa profile. Administration of the novel compounds did not reveal any abnormalities.In vivo toxicology studies did not reveal any signs of hepatoxicity with I mg/kg of compound 51. However, 10 mg/kg of compound 51 and 2 mg/kg of compound 30 revealed gross changes in the liver. Histological evidence confirmed hepatoxicity secondary to necrosis. Following preliminary dose-ranging studies in vivo, the pharmacodynamics of compound 51 and compound 30 were assessed in male C57BL/6 mice by various routes of administration. Administration of 1 mg/kg of compound 51 intraperitoneally (i.p.) and orally (p.o.) produced 40% and 60% inhibition of plasma BuChE respectively. This peripheral inhibition was relatively short-lived with recovery of plasma BuChE levels 30 minutes following i.p. and 1 hour following oral administration. 2 mg/kg of compound 30 i.p. produced approximately 25% inhibition of plasma BuChE 30 minutes following administration, with plasma BuChE levels recovering thereafter.
Keywords: Pharmacy, Ph.D.; Ph.D. Trinity College Dublin